Notas de toponimia amescoana - Segurola, Iñaki (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1987)
These notes stem from an essay by L. Michelena (cf. ASJU XIX-2 (1985) 595-602) concerning certain Basque place names from the district of Contrasta, in Alava, which have a peculiarity little remarked on until now: one of the elements in their formation is a verb form provided with a relative suffix, in particular the element dan: "in which, where is". Here we add to this a list of names of the same type, to be found in the collection of place names from Amezkoa published by Luciano Lapuente in FLV 21 (1975), 393-410, and we study various aspects of the dialectal nature of the language used there, as well as its noun formation processes. As an appendix, there is also a list of several names containing different deverbal elements, taken from documents originating in the Valley of Juslapeña, in Navarre, and in the Cendea of Cizur, in the district of Pamplona.